2020
DOI: 10.1128/aem.01486-20
|View full text |Cite
|
Sign up to set email alerts
|

Two CRISPR/Cas9 Systems Developed in Thermomyces dupontii and Characterization of Key Gene Functions in Thermolide Biosynthesis and Fungal Adaptation

Abstract: Thermomyces dupontii, a widely distributed thermophilic fungus, is an ideal organism for investigating the mechanism of thermophilic fungal adaptation to diverse environments. However, genetic analysis of this fungus is hindered by a lack of available and efficient gene manipulating tools. In this study, two different Cas9s from mesophilic and thermophilic bacteria, with in vivo sgRNA expression under the control of tRNAGly, were successfully adapted for genome editing in T. dupontii. We demonstrated the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…To investigate the function of 273, a mutant strain with 273 depletion was constructed through a modified homologous recombination . A previous study suggested that SEC metabolites were predominantly accumulated in rich nutrient medium .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate the function of 273, a mutant strain with 273 depletion was constructed through a modified homologous recombination . A previous study suggested that SEC metabolites were predominantly accumulated in rich nutrient medium .…”
Section: Resultsmentioning
confidence: 99%
“…A modified homologous recombination method , was applied to construct the vector for disruption gene 273 and mutant Δ273. All primers used in this study are provided in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations